Sainsbury’s: a campaign to raise money for schools and the environment - Mullin, Roddy (Henry Stewart Talks, 2023)
This case study showcases a promotion carried out by the retail chain Sainsbury’s as a multipurpose solution to achieving a number of business, social, and environmental objectives.